Workforce of one : revolutionizing talent management through customization - Cantrell, Susan M.; Smith, David (Harvard Business Press, 2010)
Companies have excelled by treating customers as markets of one offering them personalized buying experiences. This book shows how exceptional companies are tailoring work experiences to employees' talents and interests - customizing job duties, training, recognition, and even compensation, work schedules, and performance appraisals.